Concentration polarization and ionic conductivity of nanocomposite thermoelectric materials K0.01Cu1.94S, K0.02Cu1.94S, K0.03Cu1.94S - Kubenova, M; Kondakirov, R.E.; Alina, R.; Bekmyrza, K.Zh.; Kabyshev, A.M.; Zeleev, M.; Almukhametov, R.F.; Ishembetov, R.Kh.; Akhmetgaliev, B.; Kuterbekov, K.A.; Balapanov, M.Kh.; Kenzhebek, M.K. (Eurasian Journal of Physics and Functional Materials, 2026)
The paper presents experimental results of concentration polarization and ionic conductivity of nanocom- posite thermoelectric materials K0.01Cu1.94S , K0.02Cu1.94S , K0.03Cu1.94S . According to X-ray phase analysis, the synthesized samples are monoclinic jarleite Cu1.93÷1.97S with an admixture of oxygen ox- ide Cu2S and monoclinic chalcocyte. High values of total ionic conductivity are observed, ranging from 0.86 to 1.5 Cm/cm. The lowest ionic conductivity (0.86 Cm/cm at 355 ◦ C) is observed for alloy K0.02Cu1.94S . In addition, it was found that with an increase in the concentration of potassium in the studied materials, ionic conductivity tends to decrease, activation energy increases, but the characteris- tics of ion transport remain high, corresponding to superionic materials Recommended Citation Kubenova, M. M.; Balapanov, M. Kh.; Kuterbekov, K. A.; Akhmetgaliev, B.; Ishembetov, R. Kh.; Almukhametov, R. F.; Zeleev, M.; Kabyshev, A. M.; Bekmyrza, K. Zh.; Alina, R.; Kondakirov, R. E.; and Kenzhebek, M. K. (2024) "Concentration polarization and ionic conductivity of nanocomposite thermoelectric materials K0.01Cu1.94S, K0.02Cu1.94S, K0.03Cu1.94S," Eurasian Journal of Physics and Functional Materials: Vol. 8: No. 1, Article 5. DOI: https://doi.org/10.32523/ejpfm.2024080105